(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2026)
Natural products, renowned for their healing properties, are significant in every culture and have been practised for ages. These diverse traditional remedies, spread across various regions, are crucial in advancing humanity. In East Asian societies, conventional healing methods enjoy popularity, contrasting with the deep exploration of traditional Chinese medicine compared to traditional Indian medicine, especially in understanding their mechanisms and effects. These remedies, typically a blend of multiple herbs, target numerous cells, unlike allopathic medicine, which mainly focuses on one or two targets. Tools in network pharmacology offer extensive insights into multi-target interactions, proving invaluable in the study of herbal combinations. This analysis endeavours to uncover the potential within Ayurvedic formulations and present a global outlook on Ayurvedic research. Over time, the world has grappled with viral infections affecting the respiratory system. The study outlines the potential of Osmium tenuiflorum (Tulsi) as a remedy for Virus-induced Influenza. Initial virtual screenings suggest that Apigenin exhibits antiviral properties by influencing targets like CFTR and Akt. This review aims to draw the scientific community’s attention in that direction by highlighting Ayurvedic formulations